Four Types of ST11 Novel Mutations From Increasing Carbapenem-Resistant Klebsiella pneumoniae in Guangdong, 2016–2020 - Zhao, Yunhu; Liao, Yalong; Zhang, Ni; Liu, Suling; Zhang, Jiao; Hu, Xuejiao; Zhou, Dianrong; Deng, Qianyun; Shi, Yanping; Gu, Bing; Hou, Tieying (Frontiers in Microbiology, 2021)
Objectives: This study aimed to explore changes in carbapenem-resistant Klebsiella pneumoniae (CR-KP) isolates collected in Guangdong over the period of 2016–2020. Methods: Antibacterial susceptibility was quantified through VITEK 2 compact and K-B method. Carbapenemase phenotypes and genotypes were characterized by modified carbapenem inactivation method (mCIM), EDTA-carbapenem inactivation method (eCIM), and polymerase chain reaction (PCR). Molecular characteristics and evolutionary trends were analyzed by multilocus sequence typing and evolutionary tree. Results: Isolates (2,847) of K. pneumoniae were separated in 2016–2020, and the separate rate of CR-KP increased from 5.65 to 9.90% (p = 0.009). The top 3 wards were intensive care unit (ICU) (21.92%), neonatal wards (13.70%), and respiratory wards (12.33%). In 146 CR-KP strains, serine carbapenemase was the main phenotype, and KPC was the main genotype, and 57 contained two resistant genes, and 1 contained three resistant genes. Two polygenic strains were first found: IMP + GES and KPC + NDM + VIM, but all the phenotypes were metalloenzyme, which indicated that metalloenzyme was usually the first choice for CR-KP resistance. In addition, all the ST54 of metalloenzyme type contained IMP, and all the ST45, ST37, and ST76 contained OXA. ST11 was the most prevalent (42.47%); ST11 and its mutants proved the predominant sequence type making up 51.1% of the carbapenemase-producing isolates. A novel type of ST11 mutation, the rpoB was mutated from sequence 1 to sequence 146, was in an independent separate branch on the evolutionary tree and was resistant to all antibacterial agents. The other three mutants, rpoB 1–15, infB 3–148, and infB 3–80, are also resistant to all antibacteria. Of note, all the four mutants produced serine carbapenemase and contained KPC, and indicated that the prevalent strain in China, ST11, has serious consequences and potential outbreaks. Conclusion: The infection rate of CR-KP has increased, and ICU and neonatal wards have become the key infection areas. Producing serine enzyme, the KPC genotype, and ST11 are the predominant CR-KP. Polygenic strains and ST11 mutation made clinical treatment difficult and may become a potential threat.